1991
DOI: 10.1152/jappl.1991.70.4.1731
|View full text |Cite
|
Sign up to set email alerts
|

Stress failure in pulmonary capillaries

Abstract: In the mammalian lung, alveolar gas and blood are separated by an extremely thin membrane, despite the fact that mechanical failure could be catastrophic for gas exchange. We raised the pulmonary capillary pressure in anesthetized rabbits until stress failure occurred. At capillary transmural pressures greater than or equal to 40 mmHg, disruption of the capillary endothelium and alveolar epithelium was seen in some locations. The three principal forces acting on the capillary wall were analyzed. 1) Circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
279
0
15

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(313 citation statements)
references
References 0 publications
19
279
0
15
Order By: Relevance
“…They showed an increase in DLW and fractional 125 I-labeled albumin uptake by the lungs in the group ventilated at 45 cmH 2 O peak inspiratory pressure compared with those ventilated at 7 cmH 2 O, and ultrastructural alterations such as damage of type I cells, denuding of the epithelial basement membrane, interstitial and alveolar edema and hyaline membranes. West et al (24), using electron microscopy, demonstrated microvascular injury induced by high distending pressures. These authors detected a large number of endothelial and epithelial breaks, which they called stress fractures, at high lung volumes compared with low lung volumes.…”
Section: Discussionmentioning
confidence: 99%
“…They showed an increase in DLW and fractional 125 I-labeled albumin uptake by the lungs in the group ventilated at 45 cmH 2 O peak inspiratory pressure compared with those ventilated at 7 cmH 2 O, and ultrastructural alterations such as damage of type I cells, denuding of the epithelial basement membrane, interstitial and alveolar edema and hyaline membranes. West et al (24), using electron microscopy, demonstrated microvascular injury induced by high distending pressures. These authors detected a large number of endothelial and epithelial breaks, which they called stress fractures, at high lung volumes compared with low lung volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally VILI has been considered to be strictly related, among other mechanisms [5][6][7][8], to the application of excessive airway pressure (barotrauma) [2,9,10] and excessive tidal volume (V T , volutrauma) [11]. More recently, two different parameters describing the mechanical insult associated with ventilation have been proposed as actual determinants of VILI: lung stress, defined as the pressure developing within the lung fibrous skeleton, which equals the applied transpulmonary pressure [12], and lung strain, defined as the ratio between the lung volume variation (due to both V T and positive end-expiratory pressure, PEEP) and the lung resting volume [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid ascent to high altitude may induce in some subjects the development of pulmonary edema. Although the initial cause of alveolar flooding is likely related to altered hemodynamics or increased lung microvascular permeability (7,8), new data from human and animal studies support the concept that defective alveolar fluid clearance could have a pathogenic role in the development of high altitude pulmonary edema (HAPE) and could be a potential target for therapy. Sartori et al (9) recently reported that HAPE-sensitive subjects at low altitude have a decrease in nasal transepithelial potential difference compared with HAPE-insensitive subjects, suggesting that these subjects may have a genetically determined impairment of transepithelial sodium and liquid clearance in the lungs.…”
mentioning
confidence: 99%